1992
DOI: 10.1172/jci115832
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies associated with lupus induced by diverse drugs target a similar epitope in the (H2A-H2B)-DNA complex.

Abstract: IgG reactivity with the (H2A-H2B)-DNA complex, a subunit of the nucleosome, has been detected in many patients with lupus induced by procainamide and quinidine, but the similarity among the epitopes targeted by these antibodies in this heterogeneous patient group as well as the prevalence of this specificity in lupus induced by other drugs is unknown. Studies with histone-DNA complexes formed by sequential addition on a solid phase demonstrated that complexes containing single histones had negligible antigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…Indeed, direct antibody transfer studies have clearly demonstrated that anti-dsDNA antibodies can inflict renal pathology (34). Also consistent with this view is the observation that patients with drug-induced lupus who exhibit serum anti-H2A/H2B/DNA antibodies (in the absence of anti-dsDNA antibodies) do not go on to develop GN (35,36). However, it is intriguing to note that among the lupus patients seroprofiled by Burlingame et al (31), anti-chromatin and anti-H2A/H2B/DNA (rather than anti-dsDNA) ANAs correlated best with proteinuria.…”
Section: Figurementioning
confidence: 73%
“…Indeed, direct antibody transfer studies have clearly demonstrated that anti-dsDNA antibodies can inflict renal pathology (34). Also consistent with this view is the observation that patients with drug-induced lupus who exhibit serum anti-H2A/H2B/DNA antibodies (in the absence of anti-dsDNA antibodies) do not go on to develop GN (35,36). However, it is intriguing to note that among the lupus patients seroprofiled by Burlingame et al (31), anti-chromatin and anti-H2A/H2B/DNA (rather than anti-dsDNA) ANAs correlated best with proteinuria.…”
Section: Figurementioning
confidence: 73%
“…An F(ab')2 fragment from a patient with procainamide-induced lupus blocked > 90% of the anti-[(H2A-H2B) -DNA] reactivity in six of six sera from other patients with procainamide-induced lupus, four of four with quinidineinduced lupus, as well as sera from patients with lupus induced by acebutolol, penicillamine, and isoniazid (55). Thus, autoantibodies from humans with SLE, two strains of lupus-prone mice, and patients with lupus caused by five different drugs all recognize identical or overlapping epitopes on chromatin.…”
Section: Resultsmentioning
confidence: 98%
“…Despite a large amount of autoantibodies and abnormal lymphocyte activation, B6.Sle1 mice do not develop clinical nephritis. In many respects, this strain reflects what is seen in drug-induced lupus, which is also characterized by H2A/H2B/DNA autoantibodies in the absence of renal disease (18).…”
mentioning
confidence: 78%